Traces of trading space: Bungeng port and the horse trading system in Jeneponto 1984-2023 - Selfa; Ahmadin; Rifal; La Malihu (Research Agency for Humanity and Urban, 2026)
Bungeng Port is a center of horse trading activities, which plays a vital role in connecting Jeneponto with other regions. This study aims to determine the background of horse trading in Bungeng Port, the spatial traces of horse trading development, and the impact of horse trading on the regional economy. This study uses a qualitative approach with historical methods involving heuristics, criticism, interpretation, and historiography. Data collection was conducted through observation, interviews, and documentation. The results show that the background of horse trading is influenced by natural environmental factors, food needs, transportation, land cultivation, employment opportunities, and export-import relations between regions. Jeneponto Regency, as a center of horse trading, has become a major supplier of horses because Bungeng Port functions as a connecting space for inter-island trade. The development of horse trading is also driven by the needs of the local community, and this trade has a positive impact on the economy, increasing the trade and livestock sectors, and strengthening economic relations between Jeneponto Regency and other regions.